If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 2 = -1 Reorder the terms: 2 + -4x = -1 Solving 2 + -4x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -4x = -1 + -2 Combine like terms: 2 + -2 = 0 0 + -4x = -1 + -2 -4x = -1 + -2 Combine like terms: -1 + -2 = -3 -4x = -3 Divide each side by '-4'. x = 0.75 Simplifying x = 0.75
| w^2-6w=0 | | x+x+33+4x-31=710 | | 15+x=-10 | | 2p^2-11p+5=0 | | m+1=2 | | 4x+1-2x+1=8x+3-x+1 | | 45+67= | | x-7x-12=-20 | | A=pirh | | -3v+11=-8v+51 | | -9w+8w+3=-4 | | 2-3x=22+2x | | 4+5=27 | | 120=2x-15+7x | | 5X=0.8(-2+5X) | | 1b-9+86=30 | | m/3+m/7= | | 0.8(-2+5X)=5X | | 56.25=9x^2 | | 0.8(-2+5)=5X | | 2(4t-2)=16-2t | | -7(3w-4)=7(3w+7) | | 3x^2+x^2+12x+20=180 | | 18x-98=15x+46 | | b(5px-3c)=a(qx-4) | | 6*5-4f=26 | | 1.5(14X+2)=3(2-3X) | | t(9t+1)=8 | | 6(5-4f)=26 | | 4x+40+32y=0 | | 2*8+22c=32 | | 3x+23/5+x+10/7=9 |